LMTK3 represses tumor suppressor-like genes through chromatin remodeling in breast cancer - Xu,Y; Zhang,H; Van,TMN; Angelopoulos,N; Nunes,J; Reid,A; Buluwela,L; Magnani,L; Stebbing,J; Giamas,G (Cell Reports, 2015)
LMTK3 is an oncogenic receptor tyrosine kinase (RTK) implicated in various types of cancer, including breast, lung, gastric, and colorectal cancer. It is localized in different cellular compartments, but its nuclear function has not been investigated so far. We mapped LMTK3 binding across the genome using ChIP-seq and found that LMTK3 binding events are correlated with repressive chromatin markers. We further identified KRAB-associated protein 1 (KAP1) as a binding partner of LMTK3. The LMTK3/KAP1 interaction is stabilized by PP1α, which suppresses KAP1 phosphorylation specifically at LMTK3-associated chromatin regions, inducing chromatin condensation and resulting in transcriptional repression of LMTK3-bound tumor suppressor-like genes. Furthermore, LMTK3 functions at distal regions in tethering the chromatin to the nuclear periphery, resulting in H3K9me3 modification and gene silencing. In summary, we propose a model where a scaffolding function of nuclear LMTK3 promotes cancer progression through chromatin remodeling.